Developing an Innovative Web-Based Application for Clusterization in Healthcare - SANINFO - Viorica BADEA; Carmen RUSU; Marius GERU; Cosmin STAMATE (Modern Medicine)
The Health Information System is widely used in healthcare contexts and has improved the performance, state, and effectiveness of health services and the overall patient well-being. Following the reform of the Romanian health system, and the context created by the COVID-19 context, there is an increased demand for such platforms. In order to strengthen the Primary Health Care system, there is a need to design new services performed with the assistance of information technologies that can reduce the costs and increase the quality of the health care services. This study provides relevant information about (1) the planning and development of the health information system, (2) the needed hardware architecture, (3) the usability and design standards for health information systems, (4) the testing and validation in the local market, (5) the integration of all requirements resulting from the system testing and (6) the continuous integrations and updates. All the information obtained during the planning stage is based on previous research regarding the analysis of existing national and international online medical systems.